P024 The use of parenteral nutrition in paediatric haematology and oncology patients. Issue 7 (19th June 2019) - Whiting, Sam; Weerdenburg, Heather
Abstract : Introduction: A trust wide Parenteral Nutrition (PN) guideline is available to advise the initiating, monitoring and stopping of PN. 1 Following an increase in demand on the paediatric oncology, haematology and bone marrow transplant (BMT) ward the pharmacy and dietician team decided to audit how we use PN against these guidelines. Objectives: Is PN being started and stopped appropriately according to the nutrition guidelines? Are patients being monitored on PN appropriately? Are there alternative sources of feeding that could be initiated by enteral route prior to starting PN? Methodology: The pharmacy dispensing system was used to trace which BMT, haematology or oncology patients required parenteral nutrition. A combination of the medical notes and the electronic Medway system for those patients' notes was used to collect data. Data was collected over a 12 month period from March 2017 until February 2018, a total of 29 patients were identified and audited. Results: Alternative feeding routes to PN were deemed inappropriate in all 29 patients. A full plan had only been recorded in the patient notes in just 4% (1/29) of cases. Biochemistry was routinely provided prior to initiating PN but there was a failure to monitor patients needing long term biochemistry with only 11% (1/9) of patients having long term bloods reported. Only 38% (10/26) of patients had PN discontinued when the patient reached two-thirds of their target enteral intake. Conclusion: A plan for PN is often omitted in the medical notes. There should be an expected duration, a desired outcome, IV access and a plan around what other (if any) nutrition can be given alongside. We plan to develop a PN plan proforma which can be used to stick into the notes which prompts the medical team responsible to enter this information. There is a lack of timely long term biochemistry bloods on those patients that have PN for longer than a month. This is important clinically because long term PN patients can develop deficiency in micronutrients which need replacement. We hope that educating the medical and nursing teams about this aspect of the clinical guideline will improve our practice. Lastly, the aim of PN must be to establish nutritional requirements where otherwise calorie input would not be met. Stopping early will lead to a calorie deficit and stopping too late would mean unnecessary extra clinical risk and potential inpatient stay. There were several instances where patients would have been discharged because they were otherwise clinically well but feeds were not adequate to stop PN. Other times PN is continued at 25% of requirements, where we should be stopping as soon as patients are established on 66% of oral calorie intake. This should be part of the wider team education about PN Reference: Phipps A. April 2016, Total Parenteral Nutrition Guideline. Bristol Children's Hospital .